2005
DOI: 10.7326/0003-4819-143-9-200511010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Secondary Prevention Programs for Patients with Coronary Artery Disease

Abstract: A wide variety of secondary prevention programs improve health outcomes in patients with coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
563
2
49

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 832 publications
(627 citation statements)
references
References 89 publications
13
563
2
49
Order By: Relevance
“…Meta‐analyses suggested that CR participation can reduce all‐cause mortality by 15% to 28% for patients with MI4, 37, 38, 39 and 45% to 47% for patients with percutaneous coronary intervention 40. The effect was estimated to be comparable to improvements associated with aspirin, β‐blocker, angiotensin‐converting enzyme inhibitor, statin, and anticoagulant therapy 5, 41, 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses suggested that CR participation can reduce all‐cause mortality by 15% to 28% for patients with MI4, 37, 38, 39 and 45% to 47% for patients with percutaneous coronary intervention 40. The effect was estimated to be comparable to improvements associated with aspirin, β‐blocker, angiotensin‐converting enzyme inhibitor, statin, and anticoagulant therapy 5, 41, 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] These all report a lower all-cause mortality and death rate from cardiovascular causes in the arms who received CR rather than usual care. The reviews differ in which groups found statistically significant reductions in mortality.…”
Section: Effectiveness Of Cardiac Rehabilitationmentioning
confidence: 99%
“…As initially shown in the study by Framinhgham (3) and confirmed in subsequent studies, risk factors are ubiquitous in the world, in different racial and ethnical groups, and is closely linked to the lifestyles of populations. It has been proven that the control of risk factors through specific programs results in reduced morbidity and mortality due to cardiovascular diseases and due to all other causes (4)(5)(6) . A metanalysis revealed that regardless of strategies used to control risk factors, that is, whether the programs focus on educational strategies, physical conditioning or combined interventions, the results obtained are similar (6) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that the control of risk factors through specific programs results in reduced morbidity and mortality due to cardiovascular diseases and due to all other causes (4)(5)(6) . A metanalysis revealed that regardless of strategies used to control risk factors, that is, whether the programs focus on educational strategies, physical conditioning or combined interventions, the results obtained are similar (6) . Given the magnitude of the problem related to CVDs in the Brazilian context, it is important that nurses use a conceptual structure that enables the planning and the assessment of interventions intended to reverse this situation through the control of risk factors and illness management.…”
Section: Introductionmentioning
confidence: 99%